2008
DOI: 10.1002/dmrr.863
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic glucose production and the role of gluconeogenesis in humans: is the rate of gluconeogenesis constant?

Abstract: We have been interested in the metabolic effects of ingested fuels, both in normal subjects and in people with type 2 diabetes. Recently, we have become interested in the regulation of glucose production and the regulation of gluconeogenesis in particular. We are not aware of a recent comprehensive review of these topics. Therefore, we have reviewed the currently available literature. The pertinent papers obtained from a Medline search of the words gluconeogenesis, glycogenolysis, hepatic glucose output, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 133 publications
7
135
1
3
Order By: Relevance
“…In contrast, gluconeogenesis and its precursors (glycerol versus lactate/amino acids) was stable across 48 h of fasting, similar to other studies in fasting humans (as reviewed in Ref. 42 ). However, this fi nding differs from the expected transcriptional upregulation of genes, such as PEPCK by fasting ( 43 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, gluconeogenesis and its precursors (glycerol versus lactate/amino acids) was stable across 48 h of fasting, similar to other studies in fasting humans (as reviewed in Ref. 42 ). However, this fi nding differs from the expected transcriptional upregulation of genes, such as PEPCK by fasting ( 43 ).…”
Section: Discussionsupporting
confidence: 88%
“…Some individuals (women = 6, men = 5) were re-fed a low-fat meal (60% carbohydrate, 25% fat, and 15% protein; women = 567 and men = 667 kcal), and insulin and glucose excursion were assessed. In the 4 h after refeeding, peak insulin was signifi cantly higher in women (46 [37][38][39][40][41][42][43][44][45][46][47] vs. 20 [15][16][17][18][19][20][21][22][23][24][25] U/ml; P = 0.011), whereas peak glucose concentration did not differ between sexes ( P = 0.233). These fi ndings indicated reduced insulin sensitivity in women after short-term fasting.…”
Section: Insulin and Glucose Excursion After Refeedingmentioning
confidence: 99%
“…The glucagon rise is more persistent. In addition, our review of the literature indicated that the gluconeogenic rate is relatively constant under most circumstances (12).…”
Section: Dietary Protein Effect On Plasma Insulin and Glucagonmentioning
confidence: 89%
“…As we have pointed out previously, the role of glucagon in regulation of the glucose concentration is uncertain and appears to play only a minor role, with the exception of emergencies when additional glucose production is needed (12).…”
Section: Our Laboratory's Interest In Amino Acids In People With Typementioning
confidence: 90%
“…Hepatic gluconeogenesis is regulated within a narrow range by a number of hormonal signals translated into intracellular molecular signals (15). Among these, PGC-1a and AMPK are critical regulators of gluconeogenesis.…”
mentioning
confidence: 99%